Pengaruh Daya Tarik Iklan , Harga Dan Electronic Word Of Mouth (E-WOM) Terhadap Minat Pengguna Jasa Transportasi Online Grab (Studi pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang) - Wahyu Aerico Berliando; N. Rachma; Rahmawati Rahmawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract The development of the internet encourages innovation in various fields. So it can make it easier for someone to access everything on the internet using a smartphone/gadget which almost everyone has. With so many smartphone users, the marketing process of a business can develop more quickly online. One of the online-based businesses that is currently trending in Indonesia is the online transportation business. Determining the attractiveness of advertisements, prices and Electronic Word Of Mouth are things that are of great concern to influence the interest of service users. In this research, the Grab online transportation service was used as the research object because it has many consumers and good ratings from consumers. This research uses a quantitative approach with a sample size of 75 respondents. The data analysis methods used are instrument testing, normality testing, classical assumption testing, multiple linear regression analysis, hypothesis testing and coefficient of determination. The research results show that the variables of advertising attractiveness, price and Electronic Word Of Mouth simultaneously have a significant effect on the interest of users of the Grab online transportation service. Apart from that, the variables of advertising attractiveness, price and word of mouth partially influence the interest of users of the Grab online transportation service. In this research, the coefficient of determination value was 59.5%. Keywords: Advertising Attractiveness, Price, Word of Mouth, Service User Interest.